SCIENCE VS.RELIGION IN CLASSICAL AYURVEDA - STEVEN ENGLER (NUMEN, Vol. 50, 2003)
This paper evaluates claims that classical Ayurveda was scienti. c, in a modern western sense, and that the many religious and magical elements found in the texts were all either stale Vedic remnants or later brahminic impositions. It argues (1) that Ayurveda did not manifest standard criteria of "science" (e.g., materialism, empirical observation, experimentation, falsi. cation, quanti. cation, or a developed conception of proof) and (2) that Vedic aspects of the classical texts are too central to bem considered inauthentic or marginal. These points suggest that attempting to apply the modern western categories of "science" and "religion" to ancient South Asian medical texts at best obscures more important issues and, at worst, imports inappropriate orientalist assumptions. Having set aside the distraction of "science" vs. "religion" in classicalAyurveda, the paper . nds support for claims that brahminic elements were later additions to the texts. It concludes by arguing that this is best explained not in terms of a conceptual tension between religion and science but in terms of social and economic tensions between physicians and brahmins